Maternal depressive symptoms during immediate postpartum: associated factors - Poles, Marcela Muzel [UNESP]; Pinho Carvalheira, Ana Paula; Barros Leite Carvalhaes, Maria Antonieta de [UNESP]; Garcia de Lima Parada, Cristina Maria [UNESP] (Univ Fed Sao Paulo, Dept Enfermagen, 2018)
Objective: Investigate the prevalence and risk factors for maternal depressive symptoms in the immediate postpartum period. Methods: Cross-sectional study, involving 1099 postpartum women. The presence of maternal depressive symptoms was measured using the Edinburgh Postnatal Depression Scale, applied on the second day after birth, adopting >= 10 as a cut-off point. The data were collected in Botucatu-SP between January and June 2012. Factors associated with the depressive symptoms were initially investigated using multiple logistic regression, and those associated at the level of p<0.20 were included in the final regression model, significance being set as p<0.05, with a 95% confidence level. This study received approval from a Research Ethics Committee and complied with the recommendations for research involving human beings. Results: The prevalence of depressive symptoms amounted to 6.7%. Use of antidepressants during pregnancy, violence suffering during pregnancy and cesarean section were associated with the depressive symptoms in the immediate postpartum two, four and two times, respectively. Conclusion: Women taking antidepressants, who were victims of violence during pregnancy and who gave birth through a cesarean section need particular attention, considering that these events were identified as risk factors for depressive symptoms.
Keywords: Postpartum period; Depressive symptoms; Analytical epidemiology; Risk factors